Wanita 58 Tahun dengan Prolaps Organ Panggul dan Gangguan Berkemih Perbaikan Pasca Operasi : Laporan Kasus - Ganesha Rahman Hakim; Rodiani Rodiani (CV. Jasa Sukses Abadi, 2026)
Pelvic organ prolapse (POP) is a condition characterized by the descent of pelvic structures due to weakness of the supporting pelvic floor tissues, which is commonly found in elderly women and can cause voiding dysfunction, defecation disorders, sexual dysfunction, and decreased quality of life. This case report describes a 58-year-old woman with grade IV uterine prolapse and grade II cystocele accompanied by voiding dysfunction. Total vaginal hysterectomy (TVH) was chosen as the management because the patient was menopausal and no longer desired fertility, allowing uterine removal to correct the apical compartment while eliminating the source of prolapse. Anterior colporrhaphy was selected to repair the anterior vaginal wall defect due to pubocervical fascia weakness and to relieve mechanical obstruction of the urinary tract. The transvaginal approach was chosen due to lower morbidity, less postoperative pain, and faster recovery compared to the abdominal approach. Postoperatively, the patient showed good clinical improvement, with spontaneous voiding without straining on the second day, no major complications, and stable general condition. This case emphasizes the resolution of voiding dysfunction symptoms as the primary functional outcome, confirming that TVH and anterior colporrhaphy provide not only anatomical correction but also restoration of urinary function. Therefore, it can be concluded that appropriate surgical procedure selection based on age, hormonal status, prolapse severity, and involved compartments is essential to achieve optimal functional outcomes in patients with pelvic organ prolapse.